In-network join processing for sensor networks - YU, Hai (Institutional Knowledge at Singapore Management University, 2006)
Recent advances in hardware and wireless technologies have led to sensor networks consisting of large number of sensors capable of gathering and processing data collectively. Query processing on these sensor networks has to consider various inherent constraints. While simple queries such as select and aggregate queries in wireless sensor networks have been addressed in the literature, the processing of join queries in sensor networks remains to be investigated. In this paper, we present a synopsis join strategy for evaluating join queries in sensor networks with communication efficiency. In this strategy, instead of directly joining two relations distributed in a sensor network, synopses of the relations are firstly joined to prune those data tuples that do not contribute to join results. We discuss various issues related to the optimization of synopsis join. Through experiments, we show the effectiveness of the synopsis join techniques in terms of communication cost for different join selectivities and other parameters.